Motivational Factors in Open Access Publishing. Developing a Methodology for Evaluating Users’ Perspective of the OA Journal JeDEM - Edelmann, Noella; Schoßböck, Judith (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. JeDEM, the Journal of E-democracy and Open Government (jedem.org), was first published in 2009 as an initiative of the Centre for E-Governance. It is an open access e-journal (that follows the green open access road) with a focus on topics such as e-democracy, e-participation, open government and open access. The journal follows the green open access road, and it is indexed with EBSCO[1], DOAJ[2], Google Scholar and the Public Knowledge Project metadata harvester[3]. With a wide range of subjects and research fields, articles cover diverse topics so publishing in JeDEM attracts a wide range of authors and readers from different disciplines. While the effects and impact of open access publishing have been studied, there is less research on the motivational factors of publishing in open access e-journals (such as JeDEM) that focus on a user perspective (see e.g. Nicholas et al 2015; Jamali, Nicholas, and Herman 2016). A review of JeDEM by Quality Open Access Market (QOAM)[4] in 2016 provides an external evaluation of JeDEM, but in this contribution, we wish to present and to discuss a research design to assess the users’ perspectives and motivational factors for publishing open access whilst also considering different user types and disciplines. A workshop held at CEDEM16 (Conference for E-Democracy and Open Government 2016[5], see Lampoltshammer, Edelmann, und Schossboeck, 2016)), shed some light on the most important topics for researchers in open access publishing. The results of this workshop revealed some motivations for publishing open access. Another workshop will be held at CeDEM Asia 2016 (Conference for E-Democracy and Open Government Asia 2016)[6], with the aim of uncovering further motivational factors and understanding them from a comparative perspective. Comparing the results of both workshops and a literature review regarding motivational factors for open access publishing will form the basis for developing and choosing the questions for a quantitative study (online survey) to be sent out to all users of JeDEM by summer 2017. Conferences in the area of open access will be used to discuss the methodology and set-up of this questionnaire. Registered and potential users will be encouraged to answer the survey, also to find out about their use of the features of the journal (e.g. commenting articles) and how such features contribute to the concept of open science and scholarly communication. By assessing the user perspective of our open access journal, we seek to answer questions such as: • Can we distinguish differences in motivation for publishing in open access across user types and disciplines? What differences can be determined? • How can users be classified according to their motivations and does it make sense to consider user types and motivations for management activities of an open access journal? What type of users are JeDEM users? • What are users’ opinion on different aspects of open access publishing and its further development, e.g. open peer review etc. and how do user opinions differ across the disciplines or countries? • How can results help other e-publishers or editors in the area of open access and contribute to the field of scholarly communication? As an ongoing research project, we will be looking forward for feedback and recommendations about how to develop the user survey and our activities for the journal. [1] EBSCO Information Services www.ebsco.com [2] DOAJ Directory of Open Access Journals https://doaj.org/ [3] https://pkp.sfu.ca/ojs/ [4] https://www.qoam.eu/ [5] www.donau-uni.ac.at/cedem16 [6] www.donau-uni.ac.at/cedemasia2016